A 66 amino acid micro-peptide encoded by long non-coding RNA RP11-119F7.5 was identified in hepatocellular carcinoma. Issue 4 (2nd November 2022) - He, Chengwen; Liu, Zhiyong; Pang, Yanan; Jia, Yin; Qin, Qin; Kong, Ruijiao; Zhang, Hui; Liu, Shanrong
Abstract : Objective: Emerging data have shown that non-coding RNAs (ncRNAs) can encode micro-peptides (≤100 amino acids) that play an important role in regulating physiological and pathological processes. Herein, we explored ncRNAs that may encode micro-peptides that are involved in the development of hepatocellular carcinoma (HCC). Methods: High-throughput sequencing of ribosomal protein S6 (RPS6) was performed in four cancer cell lines using RNA-immunoprecipitation (RIP). UCSC databases obtained the full length of the gene sequences and quantitative polymerase chain reaction (qPCR) was used to evaluate expression levels of ncRNAs of interest. The coding activity of ncRNA was assessed in vitro by co-immunoprecipitation, plasmid transfection, western blot, immunofluorescence and RNA fluorescence in situ hybridization. Mass spectrometry was performed to explore the potential functions of candidate micro-peptide in HCC. This study involving human tissue specimens was conducted in accordance with Declaration of Helsinki and approved by the Institutional Review Board of Changhai Hospital, Naval Military Medical University, China (approval No. CHEC2020-081) on June 6, 2020. Results: We performed RIP assay using primary antibodies for RPS6 and high-throughput sequencing. A total of 223 overlapping genes were captured by RPS6-RIP. Venn diagram analysis revealed that 60 overlapping genes were detected in four cancer cell lines. QRT-PCR showed that six of the candidate genes (RP11-298J20.4, RP11-4O1.2, RP11-119F7.5, RP11-448G15.3, HCP5, RP11-517B11.7) were expressed in Huh7 and Hep3B cells. Further analysis of these six candidate genes and found that five (RP11-298J20.4, RP11-4O1.2, RP11-119F7.5, RP11-448G15.3, RP11-517B11.7) displayed higher expression levels in HCC cell lines (Huh7, Hep3B) and tumor tissues than in liver cell lines (L-02, QSG-7701) and non-tumor tissues, respectively. Performed additional RIP assays and confirmed that four of the genes (RP11-4O1.2, RP11-119F7.5, RP11-448G15.3, RP11-517B11.7) bound RPS6. We obtained the full length of the four gene sequences from the UCSC database and analyzed the open reading frames by ORF Finder; to determine the translation potential of the four candidate small open reading frames (smORFs), we subcloned a FLAG epitope tag into the C-terminal of the four selected smORFs before the stop codon, and the fusion sequences were then cloned into three different plasmid vectors (pSPT19, pcDNA3.1, and PEGFP-N1). We performed coupled transcription and translation reactions and found that the pSPT19 plasmids encoded small peptides in vitro . After then transfected the pcDNA3.1 constructs into Huh7 cells, and a single 7.2 kDa micro-peptide was encoded from the candidate smORF of RP11.119F7.5. We transfected the recombinant pEGFP-N1 plasmids with smORFs in HCC cells, and western blot analysis revealed a band above GFP in the RP11.119F7.5 recombinant plasmid lane. The coding potential of the RP11-119F7.5 vector was also confirmed by immunofluorescence assay. Fluorescence in situ hybridization assay revealed that RP11-119F7.5 was localized in the cytoplasm and nucleoplasm of HCC cells. Gene ontology enrichment analysis showed that the micro-peptide–interacting proteins were mainly involved in extracellular exosomes. We also found the identified proteins were involved in several biological functions like protein binding, poly(A) RNA binding, translational initiation, and the nuclear-transcribed mRNA catabolic process. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis showed the peptide-interacting proteins might participate in several critical pathways including ribosome, biosynthesis of amino acids, carbon metabolism, biosynthesis of antibiotics, glycolysis and gluconeogenesis, pathogenic Escherichia coli infection and influenza A. Conclusion: Our study revealed a novel micro-peptide translated by ncRNA RP11-119F7.5, highlighting the coding ability and potential role of ncRNAs in HCC.